2010
DOI: 10.1007/s11999-009-0944-1
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Outcome of Percutaneous Repair of Achilles Tendon Ruptures in the Elderly

Abstract: Percutaneous repair of Achilles tendon (AT) ruptures reportedly reduces the risk of rerupture compared to nonoperative treatment and reduces the risk of wound infection compared to open surgery. We retrospectively reviewed the postoperative Achilles tendon total rupture score (ATRS), and the maximum calf circumference in 35 patients over 65 years of age who sustained an acute tear of the AT and underwent percutaneous repair of the AT. There were 26 men and nine women with a mean age at operation of 73.4 ± 8.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 51 publications
3
52
0
1
Order By: Relevance
“…An up-to-date systematic review performed by Khan et al [25], along with several most recent studies [37][38][39][40][41][42], indicate that compared with open repair, percutaneous repair results in a lower complication rate. Moreover, Maffulli et al [43,44] proved that percutaneous repair of Achilles tendon was not only available for diabetic patients but also suitable for patients >65 years. Furthermore, Kosanovic et al [45] showed that percutaneous repair was effective in treating chronic Achilles tendon rupture.…”
Section: Discussionmentioning
confidence: 99%
“…An up-to-date systematic review performed by Khan et al [25], along with several most recent studies [37][38][39][40][41][42], indicate that compared with open repair, percutaneous repair results in a lower complication rate. Moreover, Maffulli et al [43,44] proved that percutaneous repair of Achilles tendon was not only available for diabetic patients but also suitable for patients >65 years. Furthermore, Kosanovic et al [45] showed that percutaneous repair was effective in treating chronic Achilles tendon rupture.…”
Section: Discussionmentioning
confidence: 99%
“…15 High rates of good and excellent outcome in young adults 16 have confirmed that new percutaneous techniques have comparable clinical effectiveness 17 and lower complication rates than open procedures. 18 These techniques are safe and effective in older individuals, 19 in diabetic patients, 20 and in high performance athletes. 21 A previously described technique 13 allows an even less invasive approach to the tendon, with appropriate apposition of the tendon ends, minimizing the risk for sural nerve injury.…”
Section: Introductionmentioning
confidence: 99%
“…Además, otros estudios 34,35 probaron que la reparación percutánea del tendón de Aquiles no solo está indicada en pacientes diabéticos, sino que también es adecuada para aquellos mayores de 65 años.…”
Section: Discussionunclassified